Utility of hybrid SPECT/CT in primary melanoma lymphoscintigraphy: A retrospective case series. Issue 2 (14th November 2016) - Tew, Khimling; Farlow, David
Abstract: Introduction: Sentinel lymph node (SLN) biopsy is widely accepted as an important part of staging cutaneous malignant melanoma. Hybrid single photon emission computed tomography and computed tomography (SPECT/CT) may identify additional SLN and provide important information to the surgeon performing SLN biopsy. We report our experience at a major referral centre for melanoma surgery. Methods: Retrospective case series of pre‐operative sentinel node lymphoscintigraphy for primary melanoma over a consecutive 12‐month period. All patients had planar imaging and hybrid SPECT/CT. Results: At least 1 SLN was successfully identified in 82 of 86 eligible patients (95.3%). These 82 patients had 144 SLNs (mean 1.8). There were no patients where the SLN was seen only with SPECT/CT. Additional information was provided by SPECT/CT in 32 patients (39.0%). Histology reports were available for 52 patients, 9 (17.3%) had at least 1 SLN positive for metastatic disease. Conclusions: We achieved a high rate of SLN identification. SPECT/CT was most frequently helpful when the primary melanoma was located in the head, neck and trunk. Routine use of SPECT/CT during lymphoscintigraphy provides important anatomical information and may reduce the false‐negative rate.